2018
DOI: 10.2147/clep.s164918
|View full text |Cite
|
Sign up to set email alerts
|

Young patients with risk factors prevalent in the elderly &ndash;&nbsp;<br />differences in comorbidity depending on severity of psoriasis: a nationwide cross-sectional study in Swedish health registers

Abstract: BackgroundAssociation between psoriasis severity and cerebro- and cardiovascular comorbidities has rarely been investigated.AimWe aimed to investigate differences in cerebro- and cardiovascular comorbidities by psoriasis severity.Materials and methodsUsing Swedish nationwide health-care registers, new adult users of anti-psoriatic drugs (2007–2013) with a recorded diagnosis of psoriasis/psoriatic arthritis or a filled prescription for calcipotriol were included. Psoriasis severity was based on the type of anti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
15
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(17 citation statements)
references
References 35 publications
2
15
0
Order By: Relevance
“…Hajiebrahimi et al found the prevalence of hypertension in psoriasis patients at 29.9% (moderate psoriasis), 32.6% (moderate-severe psoriasis), and 36.5% (severe psoriasis). 4 The French study mentioned above found the prevalence to be 26%. 12 An Australas Journal of Dermatology paper reports the rate of hypertension in psoriasis patients to be 30%, 14 as does a Brazilian study.…”
Section: Hypertensionmentioning
confidence: 93%
See 4 more Smart Citations
“…Hajiebrahimi et al found the prevalence of hypertension in psoriasis patients at 29.9% (moderate psoriasis), 32.6% (moderate-severe psoriasis), and 36.5% (severe psoriasis). 4 The French study mentioned above found the prevalence to be 26%. 12 An Australas Journal of Dermatology paper reports the rate of hypertension in psoriasis patients to be 30%, 14 as does a Brazilian study.…”
Section: Hypertensionmentioning
confidence: 93%
“…14 According to Hajiebrahimi et al, metabolic syndrome has a prevalence of 50% in psoriasis patients. 4 Argote et al also found a high 50% prevalence. 13 A similarly high finding in a study of 97 patients, reports 49.4% prevalence.…”
Section: Metabolic Syndromementioning
confidence: 94%
See 3 more Smart Citations